IOERT as anticipated tumor bed boost during breast‐conserving surgery after neoadjuvant chemotherapy in locally advanced breast cancer—Results of a case series after 5‐year follow‐up. Issue 5 (10th July 2014) - Fastner, Gerd; Reitsamer, Roland; Ziegler, Ingrid; Zehentmayr, Franz; Fussl, Christoph; Kopp, Peter; Peintinger, Florentia; Greil, Richard; Fischer, Thorsten; Deutschmann, Heinrich; Sedlmayer, Felix
<x xml:space="preserve">Abstract</x> To evaluate retrospectively rates of local (LCR) and locoregional tumor control (LRCR) in patients with locally advanced breast cancer (LABC) who were treated with preoperative chemotherapy (primary systemic treatment, PST) followed by breast‐conserving surgery (BCS) and either intraoperative radiotherapy with electrons (IOERT) preceding whole‐breast irradiation (WBI) (Group 1) or with WBI followed by an external tumor bed boost (electrons or photons) instead of IOERT (Group 2). From 2002 to 2007, 83 patients with clinical Stage II or III breast cancer were enrolled in Group 1 and 26 in Group 2. All patients received PST followed by BCS and axillary lymph node dissection. IOERT boosts were applied by single doses of 9 Gy (90% reference isodose) versus external boosts of 12 Gy (median dose range, 6–16) in 2 Gy/fraction (ICRU). WBI in both groups was performed up to total doses of 51–57 Gy (1.7–1.8 Gy/fraction). The respective median follow‐up times for Groups 1 and 2 amount 59 months (range, 3–115) and 67.5 months (range, 13–120). Corresponding 6‐year rates for LCR, LRCR, metastasis‐free survival, disease‐specific survival and overall survival were 98.5, 97.2, 84.7, 89.2 and 86.4% for Group 1 and 88.1, 88.1, 74, 92 and 92% for Group 2, respectively, without any statistical significances. IOERT as boost modality during BCS in LABC after PST shows a trend to be superior in terms of LCR and LRCR in comparison with conventional boosts.